Biblical-theological basis of Luther’s understanding about De Libero and De Servo Arbitrio - Vogel, Andre (Vox Scripturae - Revista Teológica Internacional, 2016)
This paper presents the biblical and theological understanding of Martin Luther concerning the bondage of the will and salvation. Luther outlined his beliefs in the book De Servo Arbitrio, which was written in response to Erasmus of Rotterdam’s De Libero Arbitrio Diatribe Sive Colattio. The Reformer considered De Servo Arbitrio as his most important writing, along with his Catechism. This is made readily apparent when one reads how vigorously Luther defends his biblical view concerning the subject. Therefore, this paper will begin by presenting the arguments of Erasmus in favor of free will. Then the paper will include Luther’s view upon the subject. The paper will then conclude with the author’s own personal position concerning the bondage and freedom of the will.